Heat Transfer Performance of 3D-Printed Aluminium Flat-Plate Oscillating Heat Pipes for the Thermal Management of LEDs - Chao Chang; Yaoguang Yang; Lilin Pei; Zhaoyang Han; Xiu Xiao; Yulong Ji (Micromachines, 2022)
With the rapid development of electronic technologies towards high integration, high power and miniaturization, thermal management has become an increasingly important issue to guarantee the reliability and service life of electronic devices. The oscillating heat pipe (OHP), which was governed by thermally excited oscillating motion, was considered as a promising technology to dissipate high-density heat and had excellent application prospects in many important industrial processes. A flat-plate OHP, however, was fabricated by traditional welding methods, which were difficult and inefficient, resulting in increasing the cost and wasting the production time. In this work, we adopted a new metal 3D printing technology to develop an aluminum flat-plate OHP, which made it facile to build complex inner channels with high-precision molding at one time. AlSi10Mg powders, as raw materials, were selectively melted and solidified to form the container of the flat-plate OHP. The sintered inner surface presented excellent wettability to the working fluid, which facilitated the evaporation of the working fluid. Acetone was chosen as the working fluid, and the filling ratios with a range of 40–70% were loaded into the flat-plate oscillating heat pipe to analyze its effect on heat transfer performance. It was found that the 3D-printed flat-plate OHP with a 60% filling ratio had a better heat transfer performance and a lower thermal resistance, and it was able to work properly in both vertical and horizontal operation modes. The 3D-printed flat-plate OHP had been successfully applied for the thermal management of high-power LEDs, and the results showed that the temperature of LEDs was maintained within 60 °C, and its service life was prolonged.